Contribuição da angiotensina-(1-7) no núcleop paraventricular do hipotálamo para a manutenção da pressão arterial e da atividade simpática - Ana Quenia Gomes da Silva (2007)
The hypothalamic paraventricular nucleus (PVN) is a premotor neuron cell group regulating the sympathetic vasomotor tone. Inhibition of PVN neurons with microinjection of the GABAA agonist, muscimol, reduces blood pressure (BP) and sympathetic activity. This effect is enhanced in spontaneously hypertensive rats (SHR), suggesting that hyperactivity of PVN neurons might be involved in the maintenance of the hypertensive state in these animals. Immunohistochemistry for Ang-(1-7) has been identified in several areas of the central nervous system (CNS), including PVN. Application of this peptide by microiontophoresis increases the neuronal firing rate in the PVN.The main aim of this study was to evaluate the contribution of Ang-(1-7),acting on PVN neurons, in the maintenance of sympathetic tone and BP under normal conditions or during altered states, characterized by heightened BP and sympathetic activity. Additionally, to confirm the importance of brain Ang modulating the sympathetic outflow generated by PVN neurons, we used the TGR(ASrAOGEN) (TGR) model, which expresses low levels of brain angiotensinogen (AOGEN). Under anesthesia (urethane, 1.2-1.4 g/kg of body weight i.p.), male Wistar rats (300-350g) were prepared for BP, heart rate (HR), renal sympathetic nerve activity (RSNA) recordings and craniotomy was performed to allow for microinjections into the PVN.Bilateral microinjections of Ang-(1-7) and Ang II into the PVN evoked asubstantial increase in RSNA and in a similar magnitude [Ang-(1-7): +24±8%, Ang II: +22±2% vs saline: +3±3%; P<0.05]. The blockade of endogenous Ang-(1-7) using its selective antagonist, A-779, in two doses (0.1 nmol and 1 nmol) induced a fall in RSNA comparable to that evoked by muscimol, a potent GABAA receptor agonist (low dose: -26±6%, high dose: -21±5%, Mus: -24±4% vs saline:-2±3%). Blockade of AT1 receptors for Ang II, using its selective antagonist, Losartan, reduced BP levels without changing sympathetic activity. Curiously, the blockade of AT2 receptors induced a reduction in RSNA (-22±5%), in the same magnitude, although to a different baseline response.Eucapnia and intermittent hypoxia (E-IH) cycling exposures for 14 daysinduced an increase in BP in Sprague-Dawley (SD) rats chronically infused with saline into the PVN (E-IH saline: +12±2 mmHg vs sham saline: -2±1 mmHg; P<0.01) compared to sham rats (room air exposure). Inhibition of PVN through chronic infusion of muscimol prevented the rise in BP (E-IH Mus: -9±4 mmHg), and reduced HR (E-IH Mus: -32±12 bpm vs E-IH saline: 5±9 bpm; P<0.05). The chronic blockade of Ang-(1-7) (Mas) and Ang II (AT1 and AT2) receptors prevented the increase in BP induced by E-IH exposure (E-IH A-779: -5±1 mmHg, E-IH Los: -9±4 mmHg, E-IH ZD7155: -11±4 mmHg e E-IH PD123319: -4±3 mmHg vs E-IH saline: 12±2 mmHg; P<0.05). In sham animals, BP was reduced only in the group treated with AT1 receptor antagonists (sham Los: -9±2mmHg, sham ZD7155: -6±1 mmHg vs sham saline: -2±1 mmHg; P<0.05). Plasma hyperosmolarity, induced through peripheral infusion of hypertonic saline (HTS, 2.5M) during 30 minutes in anaesthetized rats evoked an increase in BP and a reduction in RSNA levels. The blockade of endogenous Ang-(1-7), after this stimulus, induced a pronounced fall in BP (HTS A-779: -40±9 mmHg vs HTS saline: -7±3 mmHg; P<0.01) and RSNA (HTS A-779: -37±6% vs HTS saline: -2±3 %; P<0.01). Ang II blockade through AT1 receptors also induced a fall in these variables, although in a smaller magnitude (HTS Los: -16±7 mmHg; P<0.01 and HTS Los: -12±5 %; P<0.05). It is important to note that the effects ofboth A-779 and Losartan in this condition were greater than in normal animals.Neuronal inhibition of PVN in TGR(ASrAOGEN), through muscimolmicroinjections, evoked an attenuated fall in BP (TGR: -17±5 mmHg vs SD: -32±3 mmHg), HR (TGR: -23±6 bpm vs SD: -77±9 bpm) and RSNA (TGR: -3±10% vs SD: -29±8%) compared to SD animals submitted to the same protocol. These results suggest that the sympathetic tone generated by PVN is suppressed in this TGR model.Together, our results demonstrate that Ang-(1-7) contributes to themaintenance of sympathetic tone and BP exerted by PVN, through an excitatory effect. Additionally, this effect is more pronounced during E-IH exposure simulating sleep apnea and hyperosmolar conditions, suggesting that the rise in BP observed in these conditions is, at least partially, dependent upon the actions of Ang-(1-7) on PVN neurons. Finally, the importance of brain Ang, particularly Ang-(1-7), in sympathetic regulation was confirmed in that sympathetic vasomotor tone appears to be reduced in the TGR(ASrAOGEN) model.